An Electronic Frailty Index Based on Deficit Accumulation May Predict Glaucomatous Visual Field Progression - Duy W; Pajewski N; Williamson JD; Thompson AC (Clinical Ophthalmology)
Walter Duy,1,* Nicholas Pajewski,2 Jeff D Williamson,3 Atalie C Thompson3,4,* 1Wake Forest University School of Medicine, Winston-Salem, NC, USA; 2Department of Biostatistics and Data Science, Wake Forest University School of Medicine, Winston-Salem, NC, USA; 3Department of Gerontology and Geriatric Medicine, Wake Forest University School of Medicine, Winston-Salem, NC, USA; 4Department of Surgical Ophthalmology, Wake Forest University School of Medicine, Winston-Salem, NC, USA*These authors contributed equally to this workCorrespondence: Atalie C Thompson, Department of Surgical Ophthalmology, Atrium Health Wake Forest Baptist Health, Janeway Tower 6th Floor, Winston-Salem, NC, USA, Tel +1 (336) 716-4091, Fax +1 (336) 716-7994, Email atathomp@wakehealth.eduPurpose: To investigate whether an electronic frailty index (eFI) is associated with visual field loss in glaucoma.Patients and Methods: We identified 1163 subjects ≥ 65 years old with glaucoma (1082 right eyes and 1042 left eyes) who had a calculable baseline eFI, and who had reliable visual fields at baseline and final follow-up. Multivariable linear regression models adjusting for demographic and clinical variables were used to assess the association between eFI and mean deviation at baseline and the change in mean deviation over time in each eye.Results: Being pre-frail or frail was not associated with baseline MD, except in the right eye where being pre-frail was associated with a higher baseline MD. Increasing level of eFI was negatively correlated with change in MD (p< 0.05 both eyes), but not baseline MD. Moreover, being frail was significantly associated with a more significant decline in MD in both eyes (Right eye: Beta − 0.89, 95% CI (− 1.71, − 0.063), p=0.035; Left eye: Beta − 1.25, 95% CI (− 2.17, − 0.34), p=0.007). Notably, baseline IOP was not associated with MD at baseline or the change in MD in the multivariable models.Conclusion: Glaucoma patients who are frail may be at higher risk of experiencing visual field decline, independent of baseline IOP. Future studies should investigate whether interventions to improve frailty can decrease risk of glaucoma progression.Keywords: glaucoma, electronic frailty index, visual field